Axonal Transport and Local Translation of mRNA in Neurodegenerative Diseases - Nagano, Seiichi; Araki, Toshiyuki (Frontiers in Molecular Neuroscience, 2021)
Since neurons have long neurites including axons, it is crucial for the axons to transport many intracellular substances such as proteins and mitochondria in order to maintain their morphology and function. In addition, mRNAs have also been shown to be transported within axons. RNA-binding proteins form complexes with mRNAs, and regulate transport of the mRNAs to axons, as well as locally translate them into proteins. Local translation of mRNAs actively occurs during the development and damage of neurons, and plays an important role in axon elongation, regeneration, and synapse formation. In recent years, it has been reported that impaired axonal transport and local translation of mRNAs may be involved in the pathogenesis of some neurodegenerative diseases. In this review, we discuss the significance of mRNA axonal transport and their local translation in amyotrophic lateral sclerosis (ALS) / frontotemporal dementia (FTD), spinal muscular atrophy (SMA), Alzheimer's disease (AD), and fragile X syndrome (FXS).